Sensitivity of outcome instruments in a priori selected patient groups after traumatic brain injury: Results from the CENTER-TBI study. - Nicole von Steinbuechel; Katrin Rauen; Amra Covic; Ugne Krenz; Fabian Bockhop; Isabelle Mueller; Katrin Cunitz; Suzanne Polinder; Ewout W Steyerberg; Johannes Vester; Marina Zeldovich; CENTER-TBI participants investigators (PLoS ONE, 2023)
Traumatic brain injury (TBI) can negatively impact patients' lives on many dimensions. Multiple instruments are available for evaluating TBI outcomes, but it is still unclear which instruments are the most sensitive for that purpose. This study examines the sensitivity of nine outcome instruments in terms of their ability to discriminate within and between specific patient groups, selected a priori as identified from the literature, at three different time points within a year after TBI (i.e., 3, 6, and 12 months post injury). The sensitivity of the instruments to sociodemographic (sex, age, education), premorbid (psychological health status), and injury-related (clinical care pathways, TBI and extracranial injury severity) factors was assessed by means of cross-sectional multivariate Wei-Lachin analyses. The Glasgow Outcome Scale Extended (GOSE)-the standard in the field of TBI for measuring functional recovery-demonstrated the highest sensitivity in most group comparisons. However, as single functional scale, it may not be able to reflect the multidimensional nature of the outcome. Therefore, the GOSE was used as a reference for further sensitivity analyses on more specific outcome scales, addressing further potential deficits following TBI. The physical component summary score (PCS) of the generic health-related quality of life (HRQOL) instruments (SF-36v2/-12v2) and the TBI-specific HRQOL instruments (QOLIBRI/-OS) were most sensitive in distinguishing recovery after TBI across all time points and patient groups, followed by the RPQ assessing post-concussion symptoms and the PHQ-9 measuring depression. The SF-36v2/-12v2 mental component summary score and the GAD-7 measuring anxiety were less sensitive in several group comparisons. The assessment of the functional recovery status combined with generic HRQOL (the PCS of the SF-12v2), disease-specific HRQOL (QOLIBRI-OS), and post-concussion symptoms (RPQ) can provide a sensitive, comprehensive, yet time-efficient evaluation of the health status of individuals after TBI in different patient groups.